WAKAF OLEH PUTRI KETURUNAN KESULTANAN GUNUNG TABUR (Studi Kasus pada Wakaf Masjid Al-Hijrah Gunung Tabur, Berau Kalimantan Timur) - Ariffiatin, Dina Mely; Widiyanti, Dwi Retno (Islamic Economics and finance in Focus, 2023)
Management of waqf assets carried out by professional nazirs following their objectives, functions, and uses can make waqf a potential Islamic institution that is useful in strengthening the people's economy. The role of women in waqf has been seen since the time of the Prophet ﷺ. One of the women who made waqf was Hajjah Aji Putri Nural Ayani who was a descendant of the Gunung Tabur sultanate and donated her inheritance in the form of land to build a mosque. The purpose of writing this research is to find out the practice of waqf by the daughter of the descendants of the Sultanate of Mount Tabur and to find out the role of mosque waqf on Mount Tabur for the Socio-Economy of the community. This study uses a qualitative approach to the historical approach. The results of the research findings obtained that the daughter donated land to build the Al-Hijrah mosque in 1991 and the construction of the mosque was assisted by the Pancasila Muslim Amal Bakti Foundation. This mosque land waqf has a role in the fields of worship, education, social, economic, and political. There are also obstacles and challenges in the form of developing waqf assets, waqf archives, and managing human resources faced in maintaining the land waqf of the Al-Hijrah mosque.